2020
DOI: 10.1051/0004-6361/202038676
|View full text |Cite
|
Sign up to set email alerts
|

Search and analysis of giant radio galaxies with associated nuclei (SAGAN)

Abstract: Radio galaxies with jets of relativistic particles are usually hosted by massive elliptical galaxies with active nuclei powered by accretion of interstellar matter onto a supermassive black hole. In some rare cases (< 5%), their jets drive the overall structure to sizes larger than 700 kpc, and they are called giant radio galaxies (GRGs). A very small fraction of the population of such radio galaxies contains molecular and atomic gas in the form of rings or discs that can fuel star formation. The origin of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 104 publications
4
26
1
Order By: Relevance
“…Figure 1 shows that the line is well detected at the expected frequency, with a clear, although asymmetric, double-horn profile of FWHM = 684 ± 18 km s −1 and an integrated line flux of 12.6 ± 0.8 Jy km s −1 . A similar spectrum has recently been obtained by Dabhade et al (2020) who measured a somewhat greater integrated line flux of 14.0 Jy km s −1 . The difference might be due to calibration uncertainties.…”
Section: Iram/emir Single-dish Observationssupporting
confidence: 80%
See 3 more Smart Citations
“…Figure 1 shows that the line is well detected at the expected frequency, with a clear, although asymmetric, double-horn profile of FWHM = 684 ± 18 km s −1 and an integrated line flux of 12.6 ± 0.8 Jy km s −1 . A similar spectrum has recently been obtained by Dabhade et al (2020) who measured a somewhat greater integrated line flux of 14.0 Jy km s −1 . The difference might be due to calibration uncertainties.…”
Section: Iram/emir Single-dish Observationssupporting
confidence: 80%
“…The uncertainty includes only the error of the measurement, not the systematic uncertainties. Dabhade et al (2020) estimated SFR = 2.95 M yr −1 from the 22 µm flux measured with WISE, whereas Walker et al (2015) found SFR = 1.6 M yr −1 from the same GALEX UV continuum that we also used. Both adopted a Salpeter initial mass function.…”
Section: Star Formationmentioning
confidence: 96%
See 2 more Smart Citations
“…Best & Heckman 2012;Hardcastle et al 2013). Little information currently exists about the SFRs of GRGs specifically, however Clarke et al (2017) and Dabhade et al (2020c) have found evidence for moderate SFRs in several individual GRG hosts.…”
Section: Host Galaxy and Agn Characterisationmentioning
confidence: 99%